Pyridoxine-Dependent Seizures and MRI Changes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Longitudinal brain MRI findings in two patients presenting with neonatal, pyridoxine-dependent seizures and followed for 5 to 9 years are reported from the University of California, Davis, CA.